When things get dark : stories inspired by Shirley Jackson - Datlow, Ellen; Rickert, M. (Mary), 1959-; Hand, Elizabeth; McGuire, Seanan; Machado, Carmen Maria; Khaw, Cassandra; Langan, John (John Paul); Heuler, Karen; Percy, Benjamin; Oates, Joyce Carol, 1938-; Kadrey, Richard; Tremblay, Paul; et al. (Titan Books, 2021)
A collection of new and exclusive short stories inspired by, and in tribute to, Shirley Jackson. Chilling, human, poignant and strange, her stories have inspired a generation of writers and readers. This anthology, edited by legendary horror editor Ellen Datlow, will bring together today's leading horror writers to offer their own personal tribute to the work of Shirley Jackson.